Effectiveness of Digital Heat Teaching Materials Based on Science, Environment, Technology, Society (SETS) to Improve Science Literacy of Junior High School Students - Astuti, Heny Yuliana; Nugroho, Sunyoto Eko; Astuti, Budi (Universitas Negeri Semarang, 2022)
Nowadays, students need scientific literacy to develop skills to deal with technological developments in the industrial era 4.0. According to several studies, the scientific literacy of Junior High School and Islamic Junior High School students in various regions in Indonesia is in the medium and low categories. Innovative teaching materials appropriate for use in online learning are digital teaching materials. The development of SETS-based digital teaching materials is one of the efforts to improve students' scientific literacy in an online learning. The purpose of this research is to analyze how the validity, readability, and effectiveness of SETS based digital heat teaching materials improve the scientific literacy of Junior High School students. The method employed in this research was the Research and Development (R&D. It took the research sample from seventh-grade students of State Junior High School 3 Juwana by selecting three classes totalling 90 students. The expert validation of teaching materials using expert judgment obtained a score of 93.18% and the proof of media experts received 92.65%, indicating that teaching materials were suitable for learning media. The readability test results to the teaching materials using the gap test showed that the teaching materials were easy to understand. The results of the N-gain test from the pretest and posttest scores obtained a score of 0.706, which indicated that the enhancement of student’s scientific literacy was in the high category. Based on these result, it can be concluded that SETS-based digital teaching materials were effective in improving the scientific literacy of Junior High School students.